The effect of online behavioural advertising, hedonic shopping, dan shopping lifestyle on impluse buying purchase on Tokopedia - Muhammad Sulthan al Thoriq; Vidyarini Dwita (Universitas Negeri Padang, 2022)
This study is aimed to examine (1) the influence of online behavioral advertising on impulse buying (2) the influence of hedonic shopping on impulse buying (3) the influence of shopping lifestyle by impulse buying on purchased product in E-Commerce, Tokopedia, in Padang. This type of research is a quantitative research with the model design of study is Purposive Sampling. Purposive sampling is a sampling technique, within Tokopedia E-Commerce consumers in Padang City with total sample 232 respondents. This study is used primary data, which shared to E-Commerce Tokopedia consumers in Padang City who has been shop impulsively. The analytical method used is descriptive and quantitative analysis through multiple regression on SPSS 16.0 software. The results of these studies are: (1) online behavioral advertising has a significant effect on impulse buying (2) hedonic shopping has a significant effect on impulse buying (3) lifestyle shopping has a significant effect on impulse buying on purchased product in the Tokopedia E-Commerce application in Padang.